Comparative studies on GTA and PCGTA weldments of AISI 4140 and AISI 316 dissimilar metals. (24th February 2014) - Reddy, Madduru Phanindra; Prashanth, M. Mohan; William, A. Aldrin Sam; Arivarasu, M.; Ramkumar, K. Devendranath; Arivazhagan, N.; Narayanan, S.
In this study, an attempt has been made to investigate the weldability, mechanical properties of dissimilar weldments of AISI 4140 and AISI 316. These dissimilar metals were welded using gas tungsten arc welding (GTAW) and Pulsed Current GTAW (PCGTAW) employing ER309L filler wire. It was observed from the tensile test results that the fracture was occurred at the parent metal of AISI 316 in all the trials for both the weldments. On examining the SEM fractographs, the mode of fracture was found to be ductile in nature. In addition, the scanning electron microscopy and electron dispersive X–ray spectroscopy (SEM/EDS) analysis was performed at various zones of the as–welded samples of AISI 4140 and AISI 316 to reveal the structure–property relationships.